Anti‐hyperlipidaemic effects of synthetic analogues of nordihydroguaiaretic acid in dyslipidaemic rats. (10th December 2018) - Singh, Madhurima; Bittner, Stefanie; Li, Yihang; Bittner, Alex; Han, Lu; Cortez, Yuan; Inayathullah, Mohammed; Arif, Zeeshan; Parthasarathi, Ramakrishnan; Rajadas, Jayakumar; Shen, Wen‐Jun; Nicolls, Mark R; et al.
Abstract : Background and Purpose: Previous studies have shown that Creosote bush‐derived nordihydroguaiaretic acid (NDGA) exerts beneficial actions on the key components of metabolic syndrome including dyslipidaemia, insulin resistance and hypertension in several relevant rodent models. Here, we synthesized and screened a total of 6 anti‐hyperlipidaemic analogues of NDGA and tested their efficacy against hepatic lipid metabolism in a high‐fructose diet (HFrD) fed dyslipidaemic rat model. Experimental Approach: HFrD fed Sprague–Dawley rats treated with NDGA or one of the six analogues were used. Serum samples were analysed for blood metabolites, whereas liver samples were quantified for changes in various mRNA levels by real‐time RT‐PCR. Key Results: Oral gavage of HFrD‐fed rats for 4 days with NDGA analogues 1 and 2 (100 mg·kg −1 ·day −1 ) suppressed the hepatic triglyceride content, whereas the NDGA analogues 2, 3 and 4, like NDGA, decreased the plasma triglyceride levels by 70–75%. qRT‐PCR measurements demonstrated that among NDGA analogues 1, 2, 4 and 5, analogue 4 was the most effective at inhibiting the mRNA levels of some key enzymes and transcription factors involved in lipogenesis. All four analogues almost equally inhibited the key genes involved in triglyceride synthesis and fatty acid elongation. Unlike NDGA, none of the analogues affected the genes of hepatic fatty acid oxidation or transport. Conclusions and Implications: Our data suggest that NDGA analogues 1, 2, 4 and 5, particularly analogue 4, exert their anti‐hyperlipidaemic actions by negatively targeting genes of key enzymes and transcription factors involved in lipogenesis, triglyceride synthesis and fatty acid elongation. These analogues have therapeutic potential.